2021
DOI: 10.1186/s13578-021-00591-8
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative role of SIRT1 in peritoneal fibrosis: an in vivo and in vitro study

Abstract: Background Peritoneal fibrosis is one of the major complications induced by peritoneal dialysis (PD). Damaged integrity and function of peritoneum caused by peritoneal fibrosis not only limits the curative efficacy of PD and but affects the prognosis of patients. However, the detailed mechanisms underlying the process remain unclear and therapeutic strategy targeting TGF‐β is deficient. Transforming growth factor‐β (TGF‐β) signaling participates in the progression of peritoneal fibrosis through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It makes use of the peritoneal membrane (PM) of human body as a semipermeable membrane to get rid of metabolites and toxic substances in the body and correct the imbalance of water and electrolyte balance via nonstop changes of the dialysate fluid in the abdominal cavity [3,4]. However, the long-term utilization of high-glucose (HG) dialysate may also result in epithelialmesenchymal transformation (EMT) in peritoneal mesothelial cells (PMCs), leading to peritoneal fibrosis (PF) [5,6]. The development of PF is a main challenge for longterm PD [7].…”
Section: Introductionmentioning
confidence: 99%
“…It makes use of the peritoneal membrane (PM) of human body as a semipermeable membrane to get rid of metabolites and toxic substances in the body and correct the imbalance of water and electrolyte balance via nonstop changes of the dialysate fluid in the abdominal cavity [3,4]. However, the long-term utilization of high-glucose (HG) dialysate may also result in epithelialmesenchymal transformation (EMT) in peritoneal mesothelial cells (PMCs), leading to peritoneal fibrosis (PF) [5,6]. The development of PF is a main challenge for longterm PD [7].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 is a nicotinamide adenosine dinucleotide (NAD)-dependent deacetylase that is involved in regulating a variety of physiological functions and has been shown to have a therapeutic role in PF [ 80 ]. Guo et al [ 47 ] overexpressed SIRT1 in human umbilical cord-derived MSCs (hUC-MSCs) and demonstrated that SIRT1-modified hUC-MSCs exhibit improved paracrine and posttranscriptional modification abilities that attenuate peritoneal inflammation and fibrosis through the TGF-β/Smad3 pathway.…”
Section: Sources Of Stem Cells and New Treatmentsmentioning
confidence: 99%
“…TGF-beta also produces an expansion of the submesothelial extracellular matrix, making the tissue hypoxic; this hypoxia drives a secondary angiogenic response [24]. Consequently, the control of TGF-beta production represents an interesting pharmacological strategy for the prevention of peritoneal fibrosis [25][26][27][28][29].…”
Section: The Role Of Growth Factors and Cytokynesmentioning
confidence: 99%